Making scientific data available to adaptation practitioners: the Wallace Initiative and ClimaScope - Warren RF; Price JT; Vanderwal J; Ramírez Villegas, Julián Armando; Jarvis, Andy; Shoo L; Goswami S (2011)
Governments and conservation organizations have dedicated extensive resources to protect biodiversity, but their conservation strategies have largely been developed under an assumption of a static climate. These strategies may fail with changing climates, especially when combined with existing anthropogenic pressures. We designed a system to help conservationists plan for a dynamic climate: the Wallace Initiative.